2023
DOI: 10.4155/fmc-2023-0034
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Discovery of Thiosemicarbazones As SARS-CoV-2 Main Protease Inhibitors

Abstract: Aim: Discovery of novel SARS-CoV-2 main protease (Mpro) inhibitors using a structure-based drug discovery strategy. Materials & methods: Virtual screening employing covalent and noncovalent docking was performed to discover Mpro inhibitors, which were subsequently evaluated in biochemical and cellular assays. Results: 91 virtual hits were selected for biochemical assays, and four were confirmed as reversible inhibitors of SARS CoV-2 Mpro with IC50 values of 0.4–3 μM. They were also shown to inhibit SARS-Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 113 publications
0
1
0
Order By: Relevance
“…Despite the true positive rate of MSSA and MRSA models being lower in comparison to their true negative rates, our virtual screening performed equivalent or even better than other virtual screening campaigns reported in the literature. 67,68 Furthermore, we analyzed the influence of the average value of probabilities on the confusion matrix metrics (true negative rate, accuracy, and balanced accuracy). As high as the cutoff is, the predictability of models (Supporting Figure S6) suggested that this parameter should be considered in future studies as a mandatory threshold for decision making.…”
Section: Tp Tn Fp Fn (Tp Fp)(tp Fn)(tn Fp)(tn Fn)mentioning
confidence: 99%
“…Despite the true positive rate of MSSA and MRSA models being lower in comparison to their true negative rates, our virtual screening performed equivalent or even better than other virtual screening campaigns reported in the literature. 67,68 Furthermore, we analyzed the influence of the average value of probabilities on the confusion matrix metrics (true negative rate, accuracy, and balanced accuracy). As high as the cutoff is, the predictability of models (Supporting Figure S6) suggested that this parameter should be considered in future studies as a mandatory threshold for decision making.…”
Section: Tp Tn Fp Fn (Tp Fp)(tp Fn)(tn Fp)(tn Fn)mentioning
confidence: 99%